Fan translation of games, anime, and fanfiction - Vazquez-Calvo, Boris; Zhang, Leticia Tian; Pascual, Mariona; Cassany, Daniel (National Foreign Language Resource Center (NFLRC) at the University of Hawaii at Manoa, 2019)
Fan practices involving translation open up opportunities to explore language learning practices within the fandom (Sauro, 2017). We examine how three fans capitalize on fan translation and language learning. We consider the cases of Selo (an English–Spanish translator of games), Nino (a Japanese–Catalan fansubber of anime, and Alro (an English–Spanish translator of fanfics). A corpus was built consisting of 297 minutes of interviews, 186 screenshots of language learning events from online sites, and 213 minutes of screencast videos of online activity. Drawing upon the conceptual framework of new literacy studies (Barton, 2007), we set four themes to present fans’ literacy practices and language learning: (a) fan translation, (b) understanding the original text, (c) writing and preparing the translation, and (d) tools, resources, and collaborative online practices. Results indicated that the three informants encountered an open space for agency, creativity, and identity building and reinforcement through fan translation. Their translations provided content and represented the generators of the semiotic fabric in their fandoms (Gee, 2005). As fan translators, they learned language in multiple ways, such as peer-to-peer feedback, autodidactism, and creative uses of Google Translate. Future research may attempt to transfer knowledge from digital wilds into formal education.
Keywords: Lenguaje; Traducción; Etnología; Fandom; Translation; Fan practices; Language learning; CALL; Technology-enhanced language learning; Informal language learning; Informal language learning online; Digital ethnography